Knowledge levels of physicians in samsun about Patients' rights - Muhammet Ali Oruc; Bahadir Yazicioglu; Mucahit Oruc (Medicine Science, 2022)
The patient-physician relationship is an issue that includes mutual rights in medical ethics. Patient rights is one of the sub-topics of human rights that has defined and developed in the last century. In this study, it was aimed to measure the knowledge level of physicians in Samsun province about patient rights. The study is a descriptive, cross-sectional and analytical study with a prospective survey prepared by literature review to measure the knowledge level of physicians about patient rights in Samsun. The data measurement tool includes questions measuring demographic data and knowledge level and was filled with face-to-face interviews with physicians who agreed to participate in the study. SPSS package program was used in the analysis of the data. The study was conducted with 287 physicians. 49.5% of the participants in the study reported that they received training on patient rights. It has been observed that general practitioners are more knowledgeable about patient rights. Physicians at the highest rate (98.3%) stated that In health institutions, it is necessary to provide all kinds of hygienic conditions befitting human dignity, and to eliminate noise and all other disturbing factors. The medical and social benefits expected from medical research may be prioritized over the life and bodily integrity of the volunteer who consents to the research was the most negatively reported situation (13.6%). Physicians working in Samsun have a high level of awareness and perception of patient rights. Female doctors are more sensitive than male doctors in approaching patients within the framework of the principles of justice and equity, protecting privacy in case of death and hiding the diagnosis of the disease according to the psychological structure of the patient. [Med-Science 2022; 11(1.000): 233-8]